2018
DOI: 10.1021/acs.biochem.8b01075
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinity and Function of the Extremely Disordered Protein Complex Containing Human Linker Histone H1.0 and Its Chaperone ProTα

Abstract: It was recently reported that human linker histone H1.0 and its chaperone prothymosin-α (ProTα) form an extremely disordered 1:1 complex with an ultrahigh affinity (equilibrium dissociation constant K D of ∼2 × 10–12 M) measured using a single-molecule Förster resonance energy transfer method. It was hypothesized that the ultrahigh affinity and extreme disorder may be required for the chaperone function of ProTα, in which it displaces the linker histone from condensed chromatin. Here, we measure the binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
4
28
0
Order By: Relevance
“…1). The perturbation of the affinity by the fluorophores is thus small, at most on the order of thermal energy (k B T), in contrast to recent speculative concerns 16 . For comparison, a similar effect on binding free energy results from a change in solution ionic strength by a mere 10-20 mM.…”
Section: Resultsmentioning
confidence: 83%
“…1). The perturbation of the affinity by the fluorophores is thus small, at most on the order of thermal energy (k B T), in contrast to recent speculative concerns 16 . For comparison, a similar effect on binding free energy results from a change in solution ionic strength by a mere 10-20 mM.…”
Section: Resultsmentioning
confidence: 83%
“…9B). Notably, multiple theoretical and experimental studies have shown that the sequence-specific electrostatically driven interactions between disordered proteins can lead to LLPS and high affinity protein complex formation under physiological conditions, with the tendency to phase separate (or undergo 'complex coacervation') increasing as the 'blockiness' of the charge distribution increases [67][68][69][70][71][72] .…”
Section: Discussionmentioning
confidence: 99%
“…Although Cavin1 and CAV1 are associated together in caveolae, it remains unclear whether they interact with each other via direct protein-protein interactions. CAV1 has a unique structural domain architecture shared with other caveolins, consisting of an N-terminal disordered region (DR) (1-60), followed by an oligomerization domain (OD) (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80), scaffolding domain (CSD) (81-100), intramembrane domain (IMD) (101-133) and a C-terminal membrane associated a-helical domain (134-179) ( Fig. 3A; Fig.…”
Section: Cavin1 Promotes Co-phase Separation With N-terminal Regions mentioning
confidence: 99%
“…Note Added in Proof. During review, a study was published that implicated fluorophores in the strengthening of the binding affinity between two IDPs (83).…”
Section: Methodsmentioning
confidence: 99%